NARRATIVE CHARACTERISTICS OF ISABEL ALLENDE'S WORK "THE HOUSE OF THE SPIRITS" - Navarenko, Inna; Nevynna, Yuliia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2025)
The article is devoted to the study of narratology as a branch of the modern direction of the analysis of works of art in the theoretical aspect. A theoretical review of the definitions of the concept of "narratology" in foreign and domestic works on literary studies, linguistics and other related disciplines has been carried out. The typological status of the narrator in the narrative paradigm of the text has been studied and described. It has also become important to clarify the main types of narrators by functional parameters, as well as the differentiation of the basic principles for the literary text.Narratology allows for the analysis of the structural organization of a work of art and the interaction between the author and the reader, which makes it possible to objectively evaluate the results of the author's creative work. The subject of study of narratology is the nature, form and functioning of the narrative, and attention is focused on the possible relationships between the story and the narrative text.Literary works written in the style of magical realism represent the presentation of an idea in a fantastic, unreal and strange way in the most ordinary and everyday life. Magical realism seeks to give plausibility to the unreal, preserving the everyday nature of the fantastic as an attitude to life. The narrative features of the prose work of magical realism are studied as a way of conveying emotions, moods, the author's life position, and universal human values. The structure of narration typical for works of this genre is analyzed.________________References:• Genette, J. (1998). Figures III.• Brooks, C., & Warren, R. P. (1949). Theory of literature.• Marquez, G. G. (1967). One hundred years of solitude.• Allende, I. (1982). The house of spirits.• Ricardo Gullón (1973). El realismo mágico y la novela hispanoamericana.• Franz Roch (1925). Nach-Expressionismus. Magischer Realismus: Probleme der neuesten europäischen• Amelia Valcarcel (2001). La memoria y el perdón.• Luis Lial (1955). El realismo mágico en la literatura hispanoamericana.• Julio Cortázar (1963). Rayuela.• Carlos Fuentes (1958). La región más transparente.• Allende, I. (1985). Of love and shadow.• .Fuentes, C. (1975). Terra Nostra.• .Roe, L. (1995). Magical realism: Theory, history, community.• Parkinson, S. (2000). Latin American magical realism: A study.• Jamie Alzaguir (2018). Magical Realism in Latin American Literature: Definition and context.
Keywords: narratology, work of art, author, narratological concept, magical realism, discourse